Neurological Involvement in Multisystem Inflammatory Syndrome in Children: Clinical, Electroencephalographic and Magnetic Resonance Imaging Peculiarities and Therapeutic Implications. An Italian Single-Center Experience - Bova, Stefania Maria; Serafini, Ludovica; Capetti, Pietro; Dallapiccola, Andrea Riccardo; Doneda, Chiara; Gadda, Arianna; Lonoce, Luisa; Vittorini, Alessandra; Mannarino, Savina; Veggiotti, Pierangelo; , Milan MIS-C Study Group; Olivotto, Sara; et al. (Frontiers in Pediatrics, 2022)
Objective To describe neurological involvement in multisystem inflammatory syndrome in children (MIS-C) and to evaluate whether neurological manifestations are related to the degree of multiorgan involvement and inflammation. Methods The authors conducted a retrospective analysis of clinical, electroencephalographic (EEG), neuroradiological (MRI), and CSF parameters in 62 children with MIS-C (45 M, age 8 months—17 years, mean age 9 years) hospitalized between October 1, 2020 and March 31, 2022. Results Neurological involvement was documented in 58/62 (93.5%) patients. Altered mental status was observed in 29 (46.7%), focal neurological signs in 22 (35.4%), and non-specific symptoms in 54 (87%). EEG was performed in 26/62 children: 20 showed EEG slowing, diffuse or predominantly over the posterior regions. Ten patients underwent brain MRI: three showed a cytotoxic lesion of the corpus callosum. CSF analysis, performed in six patients, was normal. On the basis of the clinical and EEG findings, two profiles of neurological involvement were identified: 16/62 (26%) patients presented encephalitis with rapid-onset encephalopathy, focal neurological signs, and EEG slowing; 42/62 (68%) showed mild neurological involvement with mild or non-specific neurological signs. All patients received intravenous immunoglobulin and methylprednisolone (MTP), low-molecular-weight heparin, and therapeutic-dose anticoagulant treatment. Children with severe encephalopathy received intravenous MTP at 30 mg/kg/day for 3 days, obtaining rapid clinical and EEG improvement. Neurological assessment at discharge was normal in all cases. Children with encephalitis were younger than those without (median age 5 and 10 years, respectively); no differences between the two groups were found in the other parameters: comorbidities, fever, number of organs and systems involved, shock, hospitalization, pediatric intensive care unit admission, non-invasive ventilation, inotropic support, laboratory data. Conclusion Neurological involvement in MIS-C is frequent but not serious in most cases: around two thirds of the affected children had mild and short-lasting symptoms. It seems to be related to age, but not to the degree of multiorgan involvement and inflammation. In children with acute immune-mediated encephalitis, the clinical picture was dominated by encephalopathy that disappeared with immunomodulatory therapy. Neurological assessment allowed timely diagnosis and treatment.